Outdoor learning in higher education : educating beyond the seminar room - Garnham, Wendy; Oprandi, Paolo (Staff and educational development series., 2024)
"Outdoor Learning in Higher Education is essential reading for educational developers and academic teachers of all disciplines interested in the theory behind, and benefits of, learning outdoors. Filled with practical case studies and backed by recent research, it provides educators with the tools needed to create an effective yet inclusive learning experience for their students beyond the lecture hall or seminar room. In chapters which offer analysis, discussion of current debates and advice for good practice, the book is structured around five key themes: Theoretical perspectives and research supporting outdoor learning Health and wellbeing benefits for learners and educators Tools and techniques for teaching outdoors, including new technology Examples of effective fieldwork Crossing educational borders and implementing sustainability and the natural world into the curriculum. This key book cover issues which are relevant across all disciplines in higher education, including: experiential learning, sustainability, diversity and inclusion, and incorporating new technology. Outdoor Learning in Higher Education develops perspectives on these and other themes, while encouraging the creation of inspiring and effective learning environments"--